PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONBILITY (CSR) - Purwasih, Desy; Anjilni, Ratih Qadarti (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to examine the effect of company characteristics on the disclosure of Corporate Social Responsibility (CSR). CSR disclosure is measured by the CSRDI proxy based on the GRI indicators. The characteristics of the company consist of the size of the company which is measured using the Natural log (total assets) and Leverage is measured using the Debt to Equity Ratio proxy which is calculated by comparing the value of debt with the value of capital. The population in this study were 45 companies. The sampling technique used is purposive sampling and the number of samples is 32 companies. The model used in this study is panel data regression using the Eviews 9.0 application. The results of this study indicate that firm size and leverage have a joint effect on the disclosure of corporate social responsibility (CSR), firm size has a significant effect on the direction of the negative coefficient on the disclosure of corporate social responsibility (CSR), leverage has no significant effect on the disclosure of corporate social responsibility (CSR).